"Are we talking about the same Jin Ping Mei?" Examining the reception of the novel in Vietnam from a cultural translation studies perspective. Issue 1 (2nd January 2017) - Nguyen, Nam
Abstract: This paper is a case study showing how a literary classic like Jin Ping Mei (JPM) has been modified not only in its country of origin, but also in another receiving country through its translation due to various sociocultural, and political circumstances (especially censorship). The unawareness of textual transformations/modifications of the source text in the receiving nation will seriously entail the misunderstanding/misinterpretation of the classic over there where readers have access only to the sole translation of the work. The paper starts off with a brief survey on the circulation of JPM in Vietnam before the twentieth century, tracking its traces left in pre-modern Vietnam's texts. It will mainly deal with the 1969 modern Vietnamese translation of the novel ( JPM had never ever been translated into Vietnamese until that time). Since a translation can be both an adaptation and criticism of the source text, the paper will try to relocate the Vietnamese translation back into its reconstructed sociocultural settings, and scrutinize how its translator dealt with censorship of the time. Leaving the source text unidentified remained a common practice in Vietnam for a long time. Hence, in addition to identifying the source text of the translation, the paper also examines how the translator mystifies his source text and "retells" his JPM appropriately within his restrictively censored sociopolitical and cultural contexts. Examining the reception of JPM from a cultural translation studies perspective will reveal specific sociocultural circumstances that condition the translation.